2015
DOI: 10.2217/nnm.15.35
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of 1D- and 2D-Layered Inorganic Nanoparticles with Fibroblasts and Human Mesenchymal Stem Cells

Abstract: Aim This study investigates the effects of tungsten disulfide nanotubes (WSNTs) and molybdenum disulfide nanoplatelets (MSNPs) on fibroblasts (NIH-3T3) and mesenchymal stem cells (MSCs) to determine safe dosages for potential biomedical applications. Materials & methods Cytotoxicity of MSNPs and WSNTs (5–300 µg/ml) on NIH-3T3 and MSCs was assessed at 6, 12 or 24 h. MSC differentiation to adipocytes and osteoblasts was assessed following treatment for 24 h. Results Only NIH-3T3 cells treated with MSNPs show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 40 publications
2
18
0
Order By: Relevance
“…Similar results for CVD-grown MoS 2 were observed in both mouse embryo fibroblasts (NIH-3T3) and human adipose-derived mesenchymal stem cells (HAMSCs). 133 In particular, no significant loss of cell viability was observed for MoS 2 concentrations up to 50 μg mL −1 and 300 μg mL −1 in NIH-3T3 and HAMSCs, respectively. While most studies have found a high degree of biocompatibility for MoS 2 , a recent study by Liu et al indicated that exposure to MoS 2 induces a loss in cell viability in HepG2 cells at concentrations as low as 30 μg mL −1 .…”
Section: D Materials Hazard Assessmentmentioning
confidence: 88%
“…Similar results for CVD-grown MoS 2 were observed in both mouse embryo fibroblasts (NIH-3T3) and human adipose-derived mesenchymal stem cells (HAMSCs). 133 In particular, no significant loss of cell viability was observed for MoS 2 concentrations up to 50 μg mL −1 and 300 μg mL −1 in NIH-3T3 and HAMSCs, respectively. While most studies have found a high degree of biocompatibility for MoS 2 , a recent study by Liu et al indicated that exposure to MoS 2 induces a loss in cell viability in HepG2 cells at concentrations as low as 30 μg mL −1 .…”
Section: D Materials Hazard Assessmentmentioning
confidence: 88%
“…The encapsulation of GdI 3 in MWCNTs, and their magnetic properties, were reported recently, where the encapsulated Gd compounds remained paramagnetic, positioning it as a potential MRI contrast agent . Notably, similarly to CNTs, inorganic nanotubes (e.g., WS 2 ) can have similar potential applications for bioimaging and diagnostics ,. Compared with CNTs, the walls of WS 2 nanotubes are more resistant to irradiation, and also, are quite inert.…”
Section: Introductionmentioning
confidence: 94%
“…[22] Notably,s imilarly to CNTs,i norganic nanotubes (e.g.,W S 2 )c an have similarp otential applications for bioimaging and diagnostics. [23,24] Compared with CNTs,t he walls of WS 2 nanotubes are more resistant to irradiation, and also, are quite inert. Yet, advancedr esearch on both the metabolism and the capillary activity of these nanotubes is still required.…”
Section: Introductionmentioning
confidence: 99%
“…Various one- and two-dimensional (1-D and 2-D) carbon and inorganic nanomaterials such as carbon nanotubes, graphene, tungsten disulfide nanotubes and molybdenum disulfide nanoplatelets have been used for as therapeutic drug delivery, bioimaging, and stem cell tracking and as reinforcing agents to improve the mechanical properties of polymeric scaffolds [10-15]. Missing from the above list of reinforcing agents for biodegradable polymers for load bearing bone tissue engineering applications are boron nitrides nanoparticles, which have similar structural and in some cases superior physiochemical properties to carbon nanomaterials [16-18].…”
Section: Introductionmentioning
confidence: 99%
“…Various one-and two-dimensional (1D and 2D) carbon and inorganic nanomaterials such as CNTs, graphene, tungsten disulfide nanotubes, and molybdenum disulfide nanoplatelets have also been used for therapeutic drug delivery, bioimaging, and stem cell tracking and as reinforcing agents to improve the mechanical properties of polymeric scaffolds. [10][11][12][13][14][15] Missing from the above list of reinforcing agents for biodegradable polymers are boron nitride nanoparticles, which have similar structural, and in some cases, superior physiochemical properties compared to carbon nanomaterials. [16][17][18] It has been reported that boron nitride nanotubes (BNNTs) and boron nitride nanoplatelets (BNNPs, exfoliated from bulk boron nitride-less than 10 atomic layers) exhibit excellent mechanical properties.…”
Section: Introductionmentioning
confidence: 99%